Synergy and Harmony of the Presidential System of Multi Parties and Election to Associate Indonesia 2045 - Dody Nur Andriyan (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2019)
One of the agendas and results of the I-IV Amendment to the 1945 Constitution is to strengthen the Presidential system. Strengthening the presidential system synergized with reforming the party and election system must be carried out in order to achieve the objectives of governance and institutions in the framework of Indonesia 2045. The 2019 elections are simultaneously legislative and presidential elections as stipulated in Law Number 7 of 2017 concerning General Elections. The purpose of this article, the first simultaneous election should be legislative, presidential and regional head elections simultaneously. Secondly, there are 4 (four) objectives: 1). Effectiveness and efficiency, 2). Righteous democracy, 3). creating a solid and effective government, 4). period (periodization) that is more organized. Using the optics of constitutional law studies, and socio-legal, strengthened and enriched historical studies of presidential, party and election systems in Indonesia and comparisons with the United States, Brazil, Argentina. There are seven recommended strategies offered in the article: 1) Synergizing the Presidential Election, Legislative Elections and Regional Head Elections simultaneously in 2029, 2) Preparing the Draft Law for Regional Head Election Courts, 3) Making a blueprint of the Presidential Institution Bill, 4). Simplify party systems with an electoral threshold, 5). Simplify the number of parties in parliament with parliamentary threshold, 6). Implement a threshold presidential order to create balance in a multi-party presidential system, 7). Make changes to the Election Law and Evaluate the Proposal Election system with the Sainte-Laguë calculation method.